Social and cultural construction of healthy city in subsaharan africa: a case study of urban conflicts and modernisation agenda in ondo state, Nigeria (2015)
This paper examines the processes of transformation of the architecture and spatial character of a Nigerian city, in the achievement of a healthy and sustainable built environment. Objectives: It investigates the conflicts, tensions and negotiations that take place between those city dwellers embedded in the context of traditions and those pursuing a modernization agenda at a time when new infrastructures (hospitals, food markets and Automobile Markets) are being introduced in Akure. The study demonstrates that in order to understand how the built marketplace is made, unmade and reassembled, it is necessary to know how the worldviews of market users, sellers and policymakers are both culturally and socially constructed. Method Used: Interpretive anthropology and Actor Network Theory are used to explore the unwritten ritual practices, persistent traditional values, conflicts and socio-cultural transformations that underlie the physical built environment in which the health and social facilities are located. Findings: The research shows that the character of the built environment and social infrastructures within the city is not simply an outcome of national decision making, but is driven by the cultural preferences and diverging social interests of ‘actants ’ as they negotiate the process of change between tradition and modernity and make choices.